A new method for the simultaneous measurement of Ph-dependent cation exchange capacity and ph buffering capacity - Oorts, K.; Vanlauwe, Bernard; Pleysier, J.L.; Merckx, Roel (Wiley, 2004)
The pH dependent cation exchange capacity (CEC) and pH buffering capacity (pH BC) are two crucial properties in soil fertility management of variable charge soils. However, they are rarely measured, since most of the existing methods are cumbersome and time-consuming. We propose a new method, based on the silver-thiourea (AgTU) method, for the simultaneous measurement of pH dependent CEC and the pH BC. In general, this method consists of first increasing the pH of the soil to about pH 7 and then gradually acidifying the soil by titrating with HNO3, while measuring pH and CEC after each equilibration. This way, both CEC at different pH values and the pH BC are measured on the same sample, without the multiple washing steps needed in other procedures. Various aspects of the proposed method were tested and the results obtained were compared with the ion adsorption method. The modified AgTU method obtains field relevant results and is suitable for the routine analysis of large numbers of samples.